Tailoring Cu Electrodes for Enhanced CO2 Electroreduction through Plasma Electrolysis in Non-Conventional Phosphorus-Oxoanion-Based Electrolytes - Elnagar, Mohamed M.; Menezes, Pramod V.; Parada, Walter A.; Mattausch, Yannick; Kibler, Ludwig A.; Mayrhofer, Karl; Jacob, Timo (Chemsuschem, 2023)
This study presents a green, ultra-fast, and facile technique for the fabrication of micro/nano-structured and porous Cu electrodes through in-liquid plasma electrolysis using phosphorous-oxoanion-based electrolytes. Besides the preferential surface faceting, the Cu electrodes exhibit unique surface structures, including octahedral nanocrystals besides nanoporous and microporous structures, depending on the employed electrolyte. The incorporation of P-atoms into the Cu surfaces is observed. The modified Cu electrodes display increased roughness, leading to higher current densities for CO2 electroreduction reaction. The selectivity of the modified Cu electrodes towards C2 products is highest for the Cu electrodes treated in Na2HPO3 and Na3PO4 electrolytes, whereas those treated in Na2H2PO2 produce the most H2. The Cu electrode treated in Na3PO4 produces ethylene (23 %) at −1.1 V vs. RHE, and a comparable amount of acetaldehyde (15 %) that is typically observed for Cu(110) single crystals. The enhanced selectivity is attributed to several factors, including the surface morphology, the incorporation of phosphorus into the Cu structure, and the formation of Cu(110) facets. Our results not only advance our understanding of the influence of the electrolyte's nature on the plasma electrolysis of Cu electrodes, but also underscores the potential of in-liquid plasma treatment for developing efficient Cu electrocatalysts for sustainable CO2 conversion.
CRIS-Team Scopus Importer:2023-09-15
Keywords: CO; copper; In-liquid plasma; phosphorous-based electrolytes; surface structure